Efficiency Ranking of Photovoltaic Microinverters and Energy Yield Estimations for Photovoltaic Balcony Power Plants - Krauter, Stefan; Bendfeld, Jörg (Energies)
The market for microinverters is growing, especially in Europe. Driven by rising electricity prices and an easing in legislation since 2024, the number of mini-photovoltaic energy systems (mini-PVs) being installed is increasing substantially. Indoor and outdoor studies of microinverters have been carried out at Paderborn University since 2014. In the indoor lab, conversion efficiencies as a function of load have been measured with high accuracy and ranked according to Euro and CEC weightings; the latest rankings from 2024 are included in this paper. In the outdoor lab, energy yields have been measured using identical and calibrated crystalline silicon PV modules; until 2020, measurements were carried out using 215 Wp modules. Because of increasing PV module power ratings, 360 Wp modules were used from 2020 until 2024. In 2024, the test modules were upgraded to 410 Wp modules, taking into account the increase from 600 W to 800 W of inverter power limits, which is suitable for simplified operation permission (“plug-in”) in many European countries within a homogenised legislation area for such mini-photovoltaic energy systems or “balcony power plants”. This legislation for simplified operation also covers overpowered mini-plants, although the maximum AC output remains limited to 800 W. Presently, yield assessments are being carried out in the outdoor lab, which will take at least a year to be valid and comparable. Kits consisting of PV modules, inverters, and mounting systems are also being evaluated. Yield rankings sometimes differ from efficiency rankings due to the use of different MPPT algorithms with different MPP approach speeds and accuracies. To accelerate yield assessment, we developed a novel, simple formula to determine energy yield for any module and inverter configuration, including overpowered systems. This is a linear approach, determined by just two coefficients, a and b, which are given for several inverters. To reduce costs, inverters will be integrated into the module frame or the module terminal box in the future.

Integrating Prospective Scenarios in Life Cycle Engineering: Case Study of Lightweight Structures - Ostermann, Moritz; Grenz, Julian; Triebus, Marcel; Cerdas, Felipe; Marten, Thorsten; Tröster, Thomas; Herrmann, Christoph (Energies)
Lightweight design is a common approach to reduce energy demand in the use stage of vehicles. The production of lightweight materials is usually associated with an increase in energy demand, so the environmental impacts of lightweight structures need to be assessed holistically using a life cycle assessment. To estimate the life cycle environmental impacts of a product in its developmental stage, for example, by life cycle engineering, future changes in relevant influencing factors must be considered. Prospective life cycle assessment provides methods for integrating future scenarios into life cycle assessment studies. However, approaches for integrating prospective life cycle assessment into product development are limited. The objective of this work is to provide the methodological foundation for integrating future scenarios of relevant influencing factors in the development of lightweight structures. The applicability of the novel methodology is demonstrated by a case study of a structural component in a steel, aluminium, and hybrid design. The results show that appropriate decarbonisation measures can reduce the life cycle greenhouse gas emissions by up to 95 percent until 2050. We also found that shifts in the environmentally optimal design are possible in future scenarios. Therefore, the methodology and data provided contribute to improved decision-making in product development.
Keywords: Life Cycle Engineering; Life Cycle Assessment; Lightweight Design; Prospective LCA; Future-oriented LCA; Energy System; Material production; Sustainable production

Thermo-Hydraulic Performance of Pillow-Plate Heat Exchangers with Secondary Structuring: A Numerical Analysis - Afsahnoudeh, Reza; Wortmeier, Andreas; Holzmüller, Maik; Gong, Yi; Homberg, Werner; Kenig, Eugeny (Energies)
Pillow-plate heat exchangers (PPHEs) represent a suitable alternative to conventional shell-and-tube and plate heat exchangers. The inherent waviness of their channels promotes fluid mixing in the boundary layers and facilitates heat transfer. The overall thermo-hydraulic performance of PPHEs can further be enhanced by applying secondary surface structuring, thus increasing their competitiveness against conventional heat exchangers. In this work, various secondary structures applied on the PPHE surface were studied numerically to explore their potential to enhance near-wall mixing. Computational fluid dynamics (CFD) simulations of single-phase turbulent flow in the outer PPHE channel were performed and pressure drop, heat transfer coefficients, and overall thermo-hydraulic efficiency were determined. The simulation results clearly demonstrate a positive impact of secondary structuring on heat transfer in PPHEs.

Hybrid Energy System Model in Matlab/Simulink based on Solar Energy, Lithium-Ion Battery and Hydrogen - Möller, Marius Claus; Krauter, Stefan (Energies / Special Issue "Sustainable Energy Concepts for Energy Transition")
In this paper, a model of a hybrid, hydrogen-based energy system for a household which includes the heating sector is presended. With such an energy system it's possible to enable energy autarky over a whole year based on solar energy. The scope of this study was to present a verified hybrid energy system model created in Simulink which can be used to prospectively size future similar energy systems where hydrogen in combination with a li-ion battery shall be used as energy storage type.

Neural Network-Based Demand-Side Management in a Stand-Alone Solar PV-Battery Microgrid Using Load-Shifting and Peak-Clipping - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Energies)
Due to failures or even the absence of an electricity grid, microgrid systems are becoming popular solutions for electrifying African rural communities. However, they are heavily stressed and complex to control due to their intermittency and demand growth. Demand side management (DSM) serves as an option to increase the level of flexibility on the demand side by scheduling users’ consumption patterns profiles in response to supply. This paper proposes a demand-side management strategy based on load shifting and peak clipping. The proposed approach was modelled in a MATLAB/Simulink R2021a environment and was optimized using the artificial neural network (ANN) algorithm. Simulations were carried out to test the model’s efficacy in a stand-alone PV-battery microgrid in East Africa. The proposed algorithm reduces the peak demand, smoothing the load profile to the desired level, and improves the system’s peak to average ratio (PAR). The presence of deferrable loads has been considered to bring more flexible demand-side management. Results promise decreases in peak demand and peak to average ratio of about 31.2% and 7.5% through peak clipping. In addition, load shifting promises more flexibility to customers.
Keywords: Energy (miscellaneous); Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Electrical and Electronic Engineering; Control and Optimization; Engineering (miscellaneous); Building and Construction

Validation and Performance of Satellite Meteorological Dataset MERRA-2 for Solar and Wind Applications - Khatibi, Arash; Krauter, Stefan (Energies)
Fast-growing energy demand of the world makes the researchers focus on finding new energy sources or optimizing already-developed approaches. For an efficient use of solar and wind energy in an energy system, correct design and sizing of a power system is of high importance and improving or optimizing the process of data obtaining for this purpose leads to higher performance and lower cost per unit of energy. It is essential to have the most precise possible estimation of solar and wind energy potential and other local weather parameters in order to fully feed the demand and avoid extra costs. There are various methods for obtaining local data, such as local measurements, official organizational data, satellite obtained, and reanalysis data. In this paper, the Modern-Era Retrospective analysis for Research and Applications dataset version 2 (MERRA-2) dataset provided by NASA is introduced and its performance is evaluated by comparison to various locally measured datasets offered by meteorological institutions such as Meteonorm and Deutscher Wetterdienst (DWD, or Germany’s National Meteorological Service) around the world. After comparison, correlation coefficients from 0.95 to 0.99 are observed for monthly global horizontal irradiance values. In the case of air temperature, correlation coefficients of 0.99 and for wind speed from 0.81 to 0.99 are observed. High correlation with ground measurements and relatively low errors are confirmed, especially for irradiance and temperature values, that makes MERRA-2 a valuable dataset, considering its world coverage and availability.
Keywords: Solar irradiance; MERRA 2; Meteonorm; DWD

Heat Pump Bridge Analysis Using the Modified Energy Transfer Diagram - Schlosser, Florian; Wiebe, Heinrich; Walmsley, Timothy G.; Atkins, Martin J.; Walmsley, Michael R. W.; Hesselbach, Jens (Energies)
Heat pumps are the key technology to decarbonise thermal processes by upgrading industrial surplus heat using renewable electricity. Existing insight-based integration methods refer to the idealised Grand Composite Curve requiring the full exploitation of heat recovery potential but leave the question of how to deal with technical or economic limitations unanswered. In this work, a novel Heat Pump Bridge Analysis (HPBA) is introduced for practically targeting technical and economic heat pump potential by applying Coefficient of Performance curves into the Modified Energy Transfer Diagram (METD). Removing cross-Pinch violations and operating heat exchangers at minimum approach temperatures by combined application of Bridge Analysis increases the heat recovery rate and reduce the temperature lift to be pumped at the same time. The insight-based METD allows the individual matching of heat surpluses and deficits of individual streams with the capabilities and performance of different market-available heat pump concepts. For an illustrative example, the presented modifications based on HPBA increase the economically viable share of the technical heat pump potential from 61% to 79%.

A Review of Uncertain Decision-Making Methods in Energy Management Using Text Mining and Data Analytics - Tavana, Madjid; Shaabani, Akram; Javier Santos-Arteaga, Francisco; Raeesi Vanani, Iman (Energies)

Optimization of Cooling Utility System with Continuous Self-Learning Performance Models - Peesel, Ron-Hendrik; Schlosser, Florian; Meschede, Henning; Dunkelberg, Heiko; Walmsley, Timothy (Energies)
Prerequisite for an efficient cooling energy system is the knowledge and optimal combination of different operating conditions of individual compression and free cooling chillers. The performance of cooling systems depends on their part-load performance and their condensing temperature, which are often not continuously measured. Recorded energy data remain unused, and manufacturers’ data differ from the real performance. For this purpose, manufacturer and real data are combined and continuously adapted to form part-load chiller models. This study applied a predictive optimization algorithm to calculate the optimal operating conditions of multiple chillers. A sprinkler tank offers the opportunity to store cold-water for later utilization. This potential is used to show the load shifting potential of the cooling system by using a variable electricity price as an input variable to the optimization. The set points from the optimization have been continuously adjusted throughout a dynamic simulation. A case study of a plastic processing company evaluates different scenarios against the status quo. Applying an optimal chiller sequencing and charging strategy of a sprinkler tank leads to electrical energy savings of up to 43%. Purchasing electricity on the EPEX SPOT market leads to additional costs savings of up to 17%. The total energy savings highly depend on the weather conditions and the prediction horizon.

Design of Robust Total Site Heat Recovery Loops via Monte Carlo Simulation - Schlosser, Florian; Peesel, Ron-Hendrik; Meschede, Henning; Philipp, Matthias; Walmsley, Timothy; Walmsley, Michael; Atkins, Martin (Energies)
For increased total site heat integration, the optimal sizing and robust operation of a heat recovery loop (HRL) are prerequisites for economic efficiency. However, sizing based on one representative time series, not considering the variability of process streams due to their discontinuous operation, often leads to oversizing. The sensitive evaluation of the performance of an HRL by Monte Carlo (MC) simulation requires sufficient historical data and performance models. Stochastic time series are generated by distribution functions of measured data. With these inputs, one can then model and reliably assess the benefits of installing a new HRL. A key element of the HRL is a stratified heat storage tank. Validation tests of a stratified tank (ST) showed sufficient accuracy with acceptable simulation time for the variable layer height (VLH) multi-node (MN) modelling approach. The results of the MC simulation of the HRL system show only minor yield losses in terms of heat recovery rate (HRR) for smaller tanks. In this way, costs due to oversizing equipment can be reduced by better understanding the energy-capital trade-off.

Assessment of Flexibilisation Potential by Changing Energy Sources Using Monte Carlo Simulation - Dunkelberg, Heiko; Sondermann, Maximilian; Meschede, Henning; Hesselbach, Jens (Energies)
In the fight against anthropogenic climate change, the benefit of the integration of fluctuating renewable energies (wind and photovoltaics) into the electricity grid is a widely proved concept. At the same time, a fluctuating and decentralised supply of energy, especially at lower voltage levels, leads to a local discrepancy in the power balance between generation and consumption. A possible solution in connection with demand side management is the grid-oriented flexibilisation of energy demand. The present study shows how the use of an innovative hybrid-redundant high-temperature heat system (combined heat and power (CHP), power-to-heat system (PtH), gas boiler) can contribute to a flexibilisation of the electrical energy demand of plastics processing companies. In this context, the flexibilisation potential of a company is to be understood as the grid-related change of the energy supply through a change of the energy sources within the framework of the process heat supply. For this purpose, an omniscient control algorithm is developed that specifies the schedule of the individual system components. A sensitivity analysis is used to test the functionality of the control algorithm. Determination of the electrical flexibilisation potential is carried out via a comprehensive simulation study using Monte Carlo methods. For this purpose, the residual load curves of four characteristic distribution grids with a high share of renewable energies as well as heat load profiles of injection moulding machines are taken into consideration. A frequency distribution provides information on the electrical flexibilisation potential to be expected depending on the various combinations. The evaluation is carried out using a specially introduced logic, which identifies grid-relevant changes in the company's power consumption as flexibilisation potential based on a reference load curve. The results show that a reliable energy supply for production is possible despite flexibilisation. Depending on the grid under consideration, there are differences in the exploitation of the potential, which essentially depends on the installed renewable capacity. Depending on the scenario under consideration, an average of up to 1486 kWhel can be shifted in a positive direction and 1199 kWhel in a negative direction.